Axial Plane Rotation of the Talus in Progressive Collapsing Foot Deformity: A Weightbearing Computed Tomography Analysis. (April 2023) - Kim, Jaeyoung; Rajan, Lavan; Henry, Jensen; Mizher, Rami; Kumar, Prashanth; Srikumar, Syian; Demetracopoulos, Constantine; Ellis, Scott; Deland, Jonathan
Background: Progressive collapsing foot deformity (PCFD) is recognized as a 3-dimensional deformity centered around the talus. Previous studies have described some features of talar motion in the ankle mortise in PCFD, such as sagging in the sagittal plane or valgus tilt in the coronal plane. However, axial plane alignment of the talus in the ankle mortise in PCFD has not been investigated extensively. The purpose of this study was to examine this axial plane alignment of PCFD vs controls using weightbearing computed tomography (WBCT) images and to determine if talar rotation in the axial plane is associated with increased abduction deformity, as well as to assess the medial ankle joint space narrowing in PCFD that may be associated with axial plane talar rotation. Methods: Multiplanar reconstructed WBCT images of 79 patients with PCFD and 35 control patients (39 scans) were retrospectively analyzed. The PCFD group was divided into 2 subgroups depending on preoperative talonavicular coverage angle (TNC): moderate abduction (TNC 20-40 degrees, n=57) and severe abduction (TNC >40 degrees, n=22). Using the transmalleolar (TM) axis as a reference, the axial alignment of the talus (TM-Tal), calcaneus (TM-Calc), and second metatarsal (TM-2MT) were calculated. Difference between TM-Tal and TM-Calc was calculated to examine talocalcaneal subluxation. A second method to assess talar rotation within the mortise utilized an angle between the lateral malleolus and the talus (LM-Tal) in the axial slices of WBCT. In addition, the prevalence of medial tibiotalar joint space narrowing was assessed. These parameters were compared between the control and PCFD groups, and between moderate and severe abduction groups. Results: The talus was significantly more internally rotated with respect to the ankle TM axis and the lateral malleolus in PCFD patients compared to controls, and in the severe abduction group compared with the moderate abduction group, using both measurement methods. Axial calcaneal orientation did not differ between groups. There was significantly greater axial talocalcaneal subluxation in the PCFD group, and this was also greater in the severe abduction group. The prevalence of medial joint space narrowing was higher in PCFD patients. Conclusion: Our findings suggest that talar malrotation in the axial plane should be considered an underlying feature of abduction deformity in PCFD. The malrotation occurs in both the talonavicular and ankle joints. This rotational deformity should be corrected at the time of reconstructive surgery, especially in cases of severe abduction deformity. In addition, medial ankle joint narrowing was observed in PCFD patients, with a higher prevalence of medial ankle joint narrowing in those with severe abduction. Level of Evidence: Level III, case-control study.